Market competition and concentration in the world market of concentrated apple juice - Kurmai, Viktória (Acta Agraria Debreceniensis, 2016)
In the study, I examined the market competition and concentration in the word market of concentrated apple juice. I used RCA index to determine comparative advantages In the world China possesses the strongest comparative advantages. Besides China, Poland, Hungary, Chile, Ukraine, Turkey and Moldova possess strong comparative advantages too. I used Herfindahl-Hirschman-index to determine the market concentration. Based on it – excluding the high Chinese market share between 2006 and 2010 – the world market of concentrated apple juice can be considered as a market with a moderate concentration. Based on the secondary research the study has a detailed examination of cause and effect relationships behind the RCA and HHI index results